Adaptation of several hybrid maize in West Nusa Tenggara drylands using modified plant spacing for optimal seed and biomass productions - Syahruddin, Karlina; Suwardi, Suwardi; Priyanto, Slamet Bambang; Efendi, Roy; Herawati, Herawati; Fattah, Abdul; Rahman, Rahman; Hasbi, Hasbi; Aminah, Aminah; Fatmawati, Fatmawati; Santoso, Sigit Budi; Bidhari, Lesty Ayu; Abid, Muhammad (Universitas Padjadjaran, 2023)
Maize is a crucial multipurpose strategic food crop in Indonesia. Land expansion employing dry land, row-space technology, and suitable varieties, is emerging as the solution to fulfill the rising need for seeds and biomass. The study was carried out from August to December using a factorial randomized block design consisting of two treatment factors, namely the treatment factor of 6 varieties and 2 row-spacings, to verify the new superior hybrid maize, which is adaptable in dry land Senayan village, Poto Tano sub-district, West Sumbawa district, and West Nusa Tenggara (NTB). The results showed that JH 37 and JH 29 varieties were adaptive to be developed in dry climate dryland areas for seed and biomass production using various narrow and wide planting space system. Jakarin, Bisi 18 and HJ 21 varieties could be planted in drylands by considering the planting space system for seed or biomass production, while the Nasa 29 variety was not recommended to be planted in drylands area for seed production, but could be used for biomass production by considering a wide planting space system such as Legowo system.